A Critique on the Book Arabic Language Teaching Methods: A Critical Approach - Sajed Zare (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Teaching Arabic has recently attracted a lot of attention inside and outside of the country leading to the publication of a pile of Arabic teaching textbooks including Arabic Language Teaching Methods: A Critical Approach (Compiled by a group of authors), which attempts to review and analyze the most recent Arabic teaching approaches. The present study enjoyed an analytical-critical approach to examine the formal, structural, and content-related aspects of the textbook. The results of the study indicated that the textbook, with all its merits, suffered from some shortcomings in mechanics of writing, editing and even content-related items. The major weakness of the textbook was having no integrated approach in developing the chapters of the book. It may have happened because a group of authors has developed the textbook. Such an inconsistency can easily be observed in the lack of formal and content integrity in some parts of the textbook. Instances of such an imbalance can be located in taking an unclear approach to clarify some topics, repetition of some texts with similar wordings, and lack of cohesion in some texts when analyzing the topics.